2020
DOI: 10.1038/s41598-020-77730-7
|View full text |Cite
|
Sign up to set email alerts
|

Robust spatial ventriloquism effect and trial-by-trial aftereffect under memory interference

Abstract: Our brain adapts to discrepancies in the sensory inputs. One example is provided by the ventriloquism effect, experienced when the sight and sound of an object are displaced. Here the discrepant multisensory stimuli not only result in a biased localization of the sound, but also recalibrate the perception of subsequent unisensory acoustic information in the so-called ventriloquism aftereffect. This aftereffect has been linked to memory-related processes based on its parallels to general sequential effects in p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Equally well, a clearer head-centred advantage might have been apparent following shorter durations of adaptation than the shortest period included here (35 s). Indeed, rapid spatial recalibration effects have been reported following very short periods of adaptation of just a few seconds or even a single trial [12][13][14]. Testing shorter durations would require a radical redesign of our current paradigm, which relies on presenting repeated adapting stimuli across a range of azimuths before each test phase (35 seconds is the time required to complete one full sweep of all azimuths).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally well, a clearer head-centred advantage might have been apparent following shorter durations of adaptation than the shortest period included here (35 s). Indeed, rapid spatial recalibration effects have been reported following very short periods of adaptation of just a few seconds or even a single trial [12][13][14]. Testing shorter durations would require a radical redesign of our current paradigm, which relies on presenting repeated adapting stimuli across a range of azimuths before each test phase (35 seconds is the time required to complete one full sweep of all azimuths).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, spatial discrepancies between audio-visual stimuli induce a spatial recalibration such that the perception of auditory locations is biased in the direction of the visual offset [ 5 9 ]: the “ventriloquism aftereffect” (VAE). The VAE is observed following a diverse range of timescales of adaptation, from several minutes [ 4 , 7 , 10 , 11 ] down to just a few seconds or even a single stimulus presentation [ 12 14 ]. In a recent study we demonstrated that the VAE is underpinned by multiple recalibration mechanisms operating over different timescales, such that multiple VAEs at different temporal scales may be maintained simultaneously [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…31 healthy right-handed adults (10 males, mean age 25.5 years, range 19 - 37 years) participated in this study. Following previous studies using similar experimental protocols (Park et al, 2021; Park & Kayser, 2020, 2021) and recommendations for sample sizes in empirical psychology (Simmons et al, 2011) we aimed for a sample size of at least n=20. Of the 31 recruited participants, three had to be excluded as they did not follow the task instructions (localizing the visual rather than the auditory target in AV trials) and two exhibited a below-threshold spatial localization performance during a screening task (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Visual stimuli were projected (Acer Predator Z650, Acer Inc., New Taipei City, Taiwan) onto an acoustically transparent screen placed in front of the speakers (Screen International Modigliani, 2×1 m 2 ). The visual stimulus was a cloud of white dots distributed according to a two-dimensional Gaussian distribution (200 dots, SD of vertical and horizontal spread = 1.6°, width of a single dot = 0.12°, duration = 50 ms), which has been used in previous studies on the ventriloquism effect and aftereffect (Park et al, 2021; Park & Kayser, 2020, 2021). The visual stimuli were centred around the same five locations as the acoustic stimuli (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…We argue that this is a minor concern for two reasons. First, a one-second difference is only small in relation to the duration of the judgment itself, which was about 6 s. Second, a recent study on audio-visual integration and recalibration has directly tested the effect of temporal delays and concluded that any potential influence of memory decay is small, at best (Park and Kayser 2020). Thus, the critical temporal offset that affects integration and recalibration should be the one between stimuli, not the one between stimuli and start of the judgment.…”
Section: Superposition Of Multiple Multisensory Attractionsmentioning
confidence: 99%